An integrated approach to oral vaccination against enteric pathogens - Davitt, Christopher (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
While the majority of human pathogens infect the body through mucosal sites, most licenced vaccines are injectable. In fact the only mucosal vaccine that is widely used for infant and childhood vaccination programs is the oral polio vaccine (OPV) developed by Albert Sabin in the 1950s. While oral vaccines against Cholera, rotavirus and Salmonella typhi have been licenced, the development of vaccines against other enteric pathogens has been slow and challenging. Mucosal vaccines elicit protective immunity at the gut mucosa, in part via antigen-specific secretory immunoglobulin A (SIgA). This explains the low efficacy of injectable cholera vaccines, which have been abandoned in favour of oral cholera vaccines (OCVs). However, oral vaccines face many challenges including passage through the acidic environment of the stomach followed by the proteolytic environment of the duodenum which can lead to the destruction of vaccines. The gut innate immune system is also difficult to activate due to its predisposition towards hyporesponsiveness and tolerance. Lastly, adjuvants such as alum, incorporated in injectable vaccines to enhance their immunogenicity are lacking for the oral route.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin